Upaya Penatalaksanaan Nyeri dengan Teknik Relaksasi - Septiana Fathonah (LPPM STIKES NOTOKUSUMO YOGYAKARTA, 2015)
Pain is the most common reason people seek medical care. It is because the pain is very annoying and troublesome. A challenge for nurses to solve these problems with proper nursing care. This review aims to describe the non-pharmacological therapy in the treatment of pain, considering the number of painful problems that occure and non-pharmacological therapies that lower cause side effect. Relaxation is one of the non-pharmacological therapy for pain. Relaxation is a mind body therapy in alternative and complementary medicine (CAM). Finally, in this review discuss the focuses more on relaxation for treatment of pain.